Daniel Mollière (1848-1890), the French anatomist and surgeon, and his encounters with nosocomial infections in the operating theatre - Tsoucalas G., Laios K., Karamanou M., Sgantzos M., Androutsos G. (2016)
Daniel Mollière, was a French anatomist and surgeon, born in Lyon, who succeeded in his short life in making his mark in surgery. He was a prolific writer who left a series of medical treatises and a committed surgeon who was responsible for various significant innovative apparatuses in the medical sper. As he lived in an era when the role of microbe had already been recognized, he was among the first to use antisepsis and install extreme measures against microbes, both in the air and on the skin’. Fountains with fresh clean water, carbonic acid, cross ventilation, medical blouses, combined with Valette’s apparatus for the dressing of amputations, were some of his precautions to reduce surgical infections and post-operative mortality. © 2016, EDIMES Edizioni Medico Scientifiche. All rights reserved.